Biodegradation of benzo[a]pyrene by bacterial consortium isolated from mangrove sediment. Issue 4 (16th February 2018) - Aziz, A.; Agamuthu, P.; Alaribe, F.O.; Fauziah, S.H.
ABSTRACT: Benzo[a]pyrene is a high-molecular-weight polycyclic aromatic hydrocarbon highly recalcitrant in nature and thus harms the ecosystem and/or human health. Therefore, its removal from the marine environment is crucial. This research focuses on benzo[a]pyrene degradation by using enriched bacterial isolates in consortium under saline conditions. Bacterial isolates capable of using benzo[a]pyrene as sole source of carbon and energy were isolated from enriched mangrove sediment. These isolates were identified as Ochrobactrum anthropi, Stenotrophomonas acidaminiphila, and Aeromonas salmonicida ss salmonicida . Isolated O . anthropi and S . acidaminiphila degraded 26% and 20%, respectively, of an initial benzo[a]pyrene concentration of 20 mg/L after 8 days of incubation in seawater (28 ppm of NaCl). Meanwhile, the bacterial consortium decomposed 41% of an initial 50 mg/L benzo[a]pyrene concentration after 8 days of incubation in seawater (28 ppm of NaCl). The degradation efficiency of benzo[a]pyrene increased to 54%, when phenanthrene was supplemented as a co-metabolic substrate. The order of biodegradation rate by temperature was 30°C > 25°C > 35°C. Our results suggest that co-metabolism by the consortium could be a promising biodegradation strategy for benzo[a]pyrene in seawater.